An overview on Nanomaterials and Nanocomposites (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
In the sector of Science and Technology, Nanomaterials, Nanoparticles andNanocomposites etc. are playing their fast-expanding role. Their impact on various areas like industries, medicines, and defense and in commercial market are extending day by day. This review work is introducing them and also introducing the difference of composite, nanocomposite, and nanomaterial etc., just to create the awareness of these materials and their potential applications.The review also focuses on the synthesis modus of Nano composites, their application and their properties etc. The purpose of this study is to throw light on Nano materials and the Nano composites. Although Nano materials and Nano composites, both are different still they have a common factor which is the dimension of nanoscale order in them. The study might motivate and inspire the future researchers to do more work ahead in this direction.